The study of improvement of the ratio of longitudinal to lateral tensile strength of the tissue paper in Thai Scott Paper Mill - Yongsak Piriyakitchpaibool (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 1976